Measuring tax aggressiveness using corporate governance mechanism / Roshidah Safeei - Safeei, Roshidah (2013)
This study seeks to investigate tax aggressiveness in the top 100 Malaysian public limited companies using a corporate governance mechanism. In this study, the tax aggressiveness was proxied by the effective tax rate (ETR). The effective tax rate indicates a company’s efforts in reducing its tax payments, thus resulting in lower effective tax rate (ETR). The corporate governance mechanism could influence tax strategies of the company through its control mechanism. This study attempts to determine the relationship between board characteristics and tax aggressiveness of the top 100 Malaysian public limited companies during the period of 2008 until 2011. The data collection process involved an examination of the board characteristics, firm characteristics and tax information. The findings of this study revealed that board characteristics did not influence the tax aggressiveness. On the other hand, firm characteristics such as firm’s size and leverage had influenced the level of tax aggressiveness of top 100 Malaysian public limited companies. The empirical results indicated that the corporate governance mechanism had not influenced the tax aggressiveness among top 100 Malaysian public limited companies.